(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Background It is difficult for individuals with diabetes mellitus to manage all of their symptoms at once because the disease is often linked with hypertension and hyperlipidaemia. The quality of life for diabetic patients is further diminished by other comorbidities, such as nephropathy, anaemia, and cardiovascular disorders. A frequent way to measure glycaemic management is by looking at the haemoglobin A1c, which shows the average blood glucose levels over a few months. In order to improve illness management, it is critical to understand how comorbid diseases affect HbA1c and related metrics. Materials and Methods There were a total of 104 people who participated in the research; half of them had diabetes mellitus (DM), while the other half served as a control group. There were various demographic and anthropometric factors measured, including age, gender, weight, and the presence or absence of anaemia, nephropathy, hypertension, hyperlipidaemia, HbA1c levels, and cardiac problems. Results Researchers found that HbA1c levels were much higher in the diabetes group compared to the control group. Furthermore, hypertension and hyperlipidaemia were more common in the DM group. It was also discovered that HbA1c readings are impacted by demographic variables such as gender, age, and weight. Conclusion Patients with diabetes are more likely to have hypertension and hyperlipidaemia, and their HbA1c levels are much greater than those of non-diabetic controls. Glycaemic regulation is influenced by several factors, including gender, age, and weight. Improving patient care may be possible in the future thanks to algorithms developed using machine learning techniques that can detect these changes early.